Populism and the affective partisan space in nine European publics: Evidence from a cross-national survey - Fuller, Sam; Horne, Will; Adams, James; Gidron, Noam (Frontiers in Political Science, 2022)
While scholars increasingly link affective polarization to the rise of populist parties, existing empirical studies are limited to the effects of radical right parties, without considering the possible effects of leftist populist parties or of parties’ varying degrees of populism. Analyzing novel survey data across eight European publics, we analyze whether citizens’ affective party evaluations broadly map onto these parties’ varying degrees of populism, along with their Left-Right ideologies. We scale survey respondents’ party feeling thermometer evaluations and social distance ratings of rival partisans to estimate a two-dimensional affective partisan space for each mass public, finding that in most (though not all) publics our mappings are strongly related to the parties’ varying degrees of populism, as well as to Left-Right ideology. We substantiate these conclusions via analyses regressing respondents’ affective ratings against exogenous measures of the parties’ Left-Right ideologies and their degrees of populism. Our findings suggest that in many European publics, populism structures citizens’ affective ratings of parties (and of their supporters) to roughly the same degree as Left-Right ideology.